Register Allocation with Graph Coloring by Ant Colony Optimization - Lintzmayer, C. N.; Mulati, M. H.; da Silva, A. F. (2011 30th International Conference of the Chilean Computer Science Society, 2011)
The goal of register allocation is to allocate an unbounded number of program values to a finite number of machine registers. In this paper, we describe a new algorithm for intraprocedural register allocation called CA-RT-RA, an algorithm that extends a classic graph coloring register allocator to use our graph coloring algorithm Color Ant-RT. The experiments demonstrated that our algorithm is able to minimize the amount of spills, thereby improving the quality of the generated code. CA-RT-RA is interesting in applications where compile time is not a concern, but the code quality.